2017
DOI: 10.1159/000464253
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Ultrasound Elastography for Evaluation of Intrathoracic Lymph Nodes: A Pilot Study

Abstract: Background: Endobronchial ultrasound (EBUS) elastography is a new imaging procedure for describing the elasticity of intrathoracic lesions and providing important additional diagnostic information. Objectives: The aim of this study was to utilize the feasibility of qualitative and quantitative methods to evaluate the ability of EBUS elastography to differentiate between benign and malignant mediastinal and hilar lymph nodes (LNs) during EBUS-guided transbronchial needle aspiration (EBUS-TBNA). Methods: Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 32 publications
3
74
0
2
Order By: Relevance
“…In the study by He and colleagues [17], the quantitative method of strain ratio showed a better diagnostic yield than the semiquantitative method of the elastography score. However, in the studies by Sun [19] and Huang [21] and their colleagues, the elastography score showed better performance than the quantitative method of mean grey value. In our meta-analysis, the semiquantitative method showed a good specificity compared with the quantitative method, and there was no significant difference for the sensibility between those subgroups.…”
Section: Commentmentioning
confidence: 90%
See 3 more Smart Citations
“…In the study by He and colleagues [17], the quantitative method of strain ratio showed a better diagnostic yield than the semiquantitative method of the elastography score. However, in the studies by Sun [19] and Huang [21] and their colleagues, the elastography score showed better performance than the quantitative method of mean grey value. In our meta-analysis, the semiquantitative method showed a good specificity compared with the quantitative method, and there was no significant difference for the sensibility between those subgroups.…”
Section: Commentmentioning
confidence: 90%
“…Our literature search yielded 36 publications for consideration, 29 of which were excluded for the following reasons: 10 were review articles or comments, two were case reports, three were not written in English, seven were a letter to editor or meeting abstract, and the seven were not specified (Fig 1). The remaining seven publications met all of the inclusion criteria and were included for this meta-analysis [10,11,[17][18][19][20][21].…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…After all, except TB, the most likely result is malignancy if a patient with exudative PE has predominantly lymphocytes. Sun et al [23] concluded that endobronchial ultrasound elastography is a promising method that is used for the identification of benign and malignant lymph nodes with high SEN, SPE, and predictive accuracy, which may offer important supplementary information in endobronchial ultrasound-guided transbronchial needle aspiration cases. Karpathiou et al [24] also raise the issue that pleural frozen sections are a valuable and accurate tool in immediately diagnosing malignancy, permitting further operations like pleurodesis in the meantime.…”
Section: Discussionmentioning
confidence: 99%